The short chain fatty acid propionate stimulates GLP-1 and PYY secretion via free fatty acid receptor 2 in rodents - Psichas, A; Sleeth, M L; Murphy, K G; Brooks, L; Bewick, G A; Hanyaloglu, A C; Ghatei, M A; Bloom, S R; Frost, G (International Journal of Obesity, 2015)
Background and Objectives: The gut hormones peptide YY (PYY) and glucagon-like peptide 1 (GLP-1) acutely suppress appetite. The short chain fatty acid (SCFA) receptor, free fatty acid receptor 2 (FFA2) is present on colonic enteroendocrine L cells, and a role has been suggested for SCFAs in appetite regulation. Here, we characterise the in vitro and in vivo effects of colonic propionate on PYY and GLP-1 release in rodents, and investigate the role of FFA2 in mediating these effects using FFA2 knockout mice. Methods: We used Wistar rats, C57BL6 mice and free fatty acid receptor 2 knockout (FFA −/− ) mice on a C57BL6 background to explore the impact of the SCFA propionate on PYY and GLP-1 release. Isolated colonic crypt cultures were used to assess the effects of propionate on gut hormone release in vitro . We subsequently developed an in vivo technique to assess gut hormone release into the portal vein following colonic infusion of propionate. Results: Propionate stimulated the secretion of both PYY and GLP-1 from wild-type primary murine colonic crypt cultures. This effect was significantly attenuated in cultures from FFA2 −/− mice. Intra-colonic infusion of propionate elevated PYY and GLP-1 levels in jugular vein plasma in rats and in portal vein plasma in both rats and mice. However, propionate did not significantly stimulate gut hormone release in FFA2 −/− mice. Conclusions: Intra-colonic administration of propionate stimulates the concurrent release of both GLP-1 and PYY in rats and mice. These data demonstrate that FFA2 deficiency impairs SCFA-induced gut hormone secretion both in vitro and in vivo .